Sustainable Agriculture 2009
DOI: 10.1007/978-90-481-2666-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Soils and Food Sufficiency: A Review

Abstract: Soil degradation, caused by land misuse and soil mismanagement, has plagued humanity since the dawn of settled agriculture. Many once thriving civilizations collapsed due to erosion, salinization, nutrient depletion and other soil degradation processes. The Green Revolution of the 1960s and 1970s, that saved hundreds of millions from starvation in Asia and elsewhere, bypassed Sub-Saharan Africa. This remains the only region in the world where the number of hungry and food-insecure populations will still be on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 172 publications
(67 reference statements)
0
65
0
1
Order By: Relevance
“…). Other environmental drivers of both the quantity and quality of crop yields include pests and pathogens, and increasingly important chronic factors include rising salinity, deteriorating soils, new pests and decreasing pollinators (Lal ; Jaggard, Qi & Ober ; Potts et al . ).…”
Section: Resilience Is Manifest Over Multiple Spatial Scales In Agri‐mentioning
confidence: 99%
“…). Other environmental drivers of both the quantity and quality of crop yields include pests and pathogens, and increasingly important chronic factors include rising salinity, deteriorating soils, new pests and decreasing pollinators (Lal ; Jaggard, Qi & Ober ; Potts et al . ).…”
Section: Resilience Is Manifest Over Multiple Spatial Scales In Agri‐mentioning
confidence: 99%
“…There are a number of meta‐studies which attempt to quantify the average (environmental and yield) benefits of practices associated with CA. Lal () reviewed the literature on soil conservation globally and concluded that mulching and no‐till clearly improved soil health, sometimes improved yields (depending on conditions) and usually improved profits (due to lower inputs). Farooq et al .…”
Section: Productivity Implications In the Literaturementioning
confidence: 99%
“…In addition to providing a stable store of soil organic matter, biochar increases soil pH and cation exchange capacity, improves soil structure and water retention capacity, and decreases nutrient loss through leaching and runoff (Lehmann, ; Sohi et al ., ; Spokas et al ., ; Glaser, ; Paz‐Ferreiro et al ., ). The benefits of biochar are evident in the nutrient‐rich terra preta (black) soils of the Amazon basin (Glaser, ; Lal, ; Lehmann, ; Barrow, ; Thomas & Gale, ). Amazonian Dark Earths are anthropogenic in origin, formed by pre‐Columbian inhabitants at settlement sites (Woods & Denevan, ).…”
Section: Introductionmentioning
confidence: 99%